Advances and applications of nanoparticles in cancer therapy - Xianzhou Huang; Tao He; Xiuqi Liang; Zhongzheng Xiang; Chao Liu; Shiyao Zhou; Rui Luo; Liping Bai; Xiaorong Kou; Xinchao Li; Rui Wu; Xinyu Gou; et al. (MedComm – Oncology, 2024)
Abstract Rapid growth in nanoparticles (NPs) as delivery systems holds vast promise to promote therapeutic approaches for cancer treatment. Presently, a diverse array of NPs with unique properties have been developed to overcome different challenges and to achieve sophisticated delivery routes for enhancement of a series of therapies. Inspiring advances have been achieved in the field of cancer therapy using NPs. In this review, we aim to summarize the up‐to‐date progression of NPs for addressing various challenges, and expect to elicit novel and potential opportunities alternatively. We first introduce different sorts of NP technologies, illustrate their mechanisms, and present their applications. Then, the achievements made by NPs to break obstacles in delivering cargoes to specific sites through particular routes are highlighted, including long‐circulation, tumor targeting, responsive release, and subcellular localization. We subsequently retrospect recent research of NPs in different cancer treatments from single therapy, like chemotherapy, to combination therapy, like chemoradiotherapy, and to integrative therapy. Finally, the challenges and perspectives of NPs in cancer therapy, and their potential impact on the field of oncology are discussed. We believe this review can offer a deeper understanding of the challenges and opportunities of NPs for cancer therapy.